2008
DOI: 10.1038/sj.bjc.6604317
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 mRNA levels and survival of advanced gastric cancer patients treated with a modified FOLFOX regimen

Abstract: Molecular markers involved in DNA repair can help to predict survival in gastric cancer patients treated with 5-FU plus platinum chemotherapy. Excision repair cross-complementing 1 (ERCC1) and thymidylate synthase (TS) mRNA expression levels were assessed in advanced gastric cancer tumour samples using real-time quantitative PCR in 76 patients treated with a modified FOLFOX (biweekly oxaliplatin plus 5-FU and folinic acid) regimen. Median survival time in patients with low ERCC1 levels was significantly longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 36 publications
6
27
3
2
Order By: Relevance
“…However, most of those studies focused on the influence of ERCC1 expression on the effect of platinum-drug in advanced or metastatic diseases, little was known about its effect on platinum-drug adjuvant chemotherapy. Our results suggested that low ERCC1 mRNA level appeared to be an independent prognostic factor for better prognosis, which is consistent with the results observed in advanced gastric cancer [30][31][32] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, most of those studies focused on the influence of ERCC1 expression on the effect of platinum-drug in advanced or metastatic diseases, little was known about its effect on platinum-drug adjuvant chemotherapy. Our results suggested that low ERCC1 mRNA level appeared to be an independent prognostic factor for better prognosis, which is consistent with the results observed in advanced gastric cancer [30][31][32] .…”
Section: Discussionsupporting
confidence: 82%
“…In advanced gastric cancer patients treated with 5-FU and oxaliplatin, favorable response rate and survival were also found in patients without ERCC1 protein expression [7] . Other studies showed that the low intratumoral ERCC1 mRNA expression was associated with favorable clinical outcomes after treatment with platinum-based chemotherapy in lung cancer [27,28] , colorectal cancer [29] , gastric cancer [30][31][32] , ovarian cancer [33] , bladder cancer [34] , head and neck cancer [35] . A recent phase Ⅲ trial in nonsmall-cell lung cancer also demonstrated that assessment of intratumoral ERCC1 mRNA expression is feasible in the clinical setting and predicts response to cisplatin [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Later studies confirmed the predictive role of ERCC1 in NSCLC [12,37] and other types of cancer, such as colorectal cancer [17], gastric carcinoma [16,[38][39], and esophageal cancer [40]. Our study showed that patients with lower expression of ERCC1 had relatively higher DCR than patients with higher gene expression when they received platinum-based chemotherapy, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have shown that expression of TS and ERCC1 has predictive value of response to chemotherapy and survival in advanced gastric cancer patients receiving systemic chemotherapy with 5-FU and platinum-based regimens [22][23][24][28][29][30][31]. Recently, Kwon et al reported a significant correlation between high expression of ERCC1 and poor survival in 64 advanced gastric cancer patients treated with FOLFOX using immunohistochemical staining [29].…”
Section: Discussionmentioning
confidence: 99%